Answer:
the 3rd one
Step-by-step explanation:
Answer:
Step-by-step explanation:
This isn't the same thing although you will get some factors that have i in them
(x^4 - 64) factors using the difference of squares.
(x^2 - 8)(x^2 + 8) Both of these factor using the difference of squares.
(x^2 - 8): factors into (x + sqrt(8) )(x - sqrt(8) )
(x^2 - 8): factors further (x + 2*sqrt2)(x - 2sqrt(2)
(x ^2 + 8) : (x + sqrt(8)i ) (x - sqrt(8)i )
(x^2 + 8) : (x + 2sqrt(2)i) (x - 2sqrt(2)i)
Final answer
(x + 2*sqrt2)(x - 2sqrt(2)(x + 2*sqrt2)(x - 2sqrt(2)
Answer:
x=36
Step-by-step explanation:
if PQR is isosceles then
PRQ will also equal 69 degrees
straight line = 180 degrees
so if PRQ is 69, then
PRS = 180-69
= 111 degrees
now to find x , since we have two angles within that triangle
180 - 111 - 33 = 36 degrees
The square root is 6 because 6*6=36